Análisis del sistema de alerta al usuario de los primeros radares de la ciudad de Babahoyo - Jaramillo Mendoza, Evelyn Katherine (2021)
With the boom in the growth of incidents and infractions generated by the system of photo-radars and photo-fines, the need to study the alert system to the user of the first radars of the Babahoyo city is born due to the transmission and lack of early synchronization with the traffic lights and the problems regarding electric shocks and voltage variations that often occur in the city; Allow this increase in monetary violations generated by the ATM in recent years.